The Transformation of Fiqh Siyasah in the Context of Pancasila Democracy: A Study of Religious Moderation and National Insight Based on Ahlussunnah Wal Jamaah - Sahal Abidin (Asian Journal of Applied Education (AJAE), 2026)
This research aims to examine the transformation of fiqh siyasah in the context of Pancasila democracy in Indonesia by emphasizing the role of religious moderation, national insight, and the perspective of Ahlussunnah wal Jamaah (Aswaja). This study uses a literature study method with a qualitative-descriptive-analytical approach. Data were obtained from a variety of relevant classical and contemporary literature, then analyzed using content analysis techniques. The results of the study show that fiqh siyasah has undergone a shift from a normative approach to a more adaptive contextual approach to the Pancasila democratic system. Religious moderation and national insight play an epistemological role as an epistemological instrument in shaping an inclusive, tolerant, and public-benefit interpretation of fiqh. Aswaja's perspective provides a methodological foundation that emphasizes a balance between text and context. This research confirms that the transformation of fiqh siyasah is able to strengthen the harmony between Islam and the state and contribute to social and political stability in Indonesia.